Legal Status Of Indıvıdual Crypto Assets As Tax Objects From Sharıa Perspectıve - Muhammad Fajaruddin Shiroth; Sukarmi Sukarmi; Reka Dewantara (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
With the rapid development of technology in the current era of progress, some people, or in this case, a tech-savvy society stores their assets in crypto assets. And they are considering that the potential of crypto assets in the stage is developing and increasing its users daily and that most Indonesian people are Muslims with the concept of wealth zakat. This study aims to determine the legal status of individual crypto assets as tax objects from a Sharia perspective. This research is normative juridical research, with research methods of statutory approach (Statue Approach), conceptual approach (Conceptual Approach) and comparative legal approach (Comparison Approach). Legal materials obtained, Primary, secondary and tertiary, are then analyzed by Grammatical and Systematic interpretation methods, where this method uses language interpretation by giving meaning to a foreign term in everyday language or legal language to provide appropriate understanding and systematically compiling and collating between appropriate laws or regulations to produce coherent research results. The results of this study state that the answer to the permissibility of storing Crypto assets as an investment with certain criteria that Bappebti has regulated as the institution responsible for the implementation of Cryptocurrency Futures Exchange trading. By paying attention to the points described in the Discussion chapter. The imposition of taxes and zakat on crypto assets cannot be done based on the argument that crypto assets are taxed in terms of increasing their value, while in the zakat mechanism, crypto assets can only be issued zakat if the nominal has reached one nishab and with full ownership for one year (haul)